Economic security of the regions: comparative analysis of approaches and construction of the technology of assessment - Rayevnyeva, Olena; Aksonova, Iryna; Derykhovska, Viktoriia; Brovko, Olha (Primedia eLaunch LLC, 2019)
In today's conditions of country's development, the economic security of the regions serves as a guarantor of the independence of the territory and an indicator of its economic growth. Economic security acts as one of the components of national security and it is impossible to carry out effectively tasks for its maintenance without understanding of its essence. At the same time, the country's economic security is determined by the level of economic security of regional systems, the justified management of which requires an objective assessment of the state and development trends based on indicators of economic security. The purpose of the research is to generalize theoretical and analytical as well as methodological foundations for determining the level of the region economic security, the integral assessment technology formation and clustering of the regions of Ukraine according to the components of economic security. There were used the system approach, logical-comparative analysis, generalization method of information, methods of taxonomy and multivariate analysis during economic security research of the regions. Monographs of scientists from the mentioned issues, materials of periodicals, statistical information of the sites of the State Statistics Service of Ukraine, Main regional statistics officesismethodological and informational basis of the research. The research presents the results of calculating the integral indicators of economic security of Ukrainianregions for 64 indicators during 2015-2017. In terms of economic security there were applied cluster and discriminant analyses for the allocation of homogeneous groups of regions. In order to identify the factors having a negative impact on state of the general level of economic security of the regions, a correlation-regression model was built for each cluster. The results of the analysis demonstrate a low level of economic security of the regions of Ukraine. An integrated assessment of the economic security level of the regions made it possible to carry out a comparative analysis that identified the most volatile (weak, vulnerable) regions and showed according to which components of economic security should make the priority management impacts. In order to develop priority tactical and strategic measures to stabilize and increase the level of economic security of the regions their clusterization and analysis of cluster migration of the regions was carried out was. As a result of the use of multifactor econometric modeling, the weights of the impact of a specific structural component of economic security on its overall level for invariant regions are determined, and in accordance with this, a set of management recommendations for improving the economic security of the country's regions is formed.
Keywords: monograph; economic security; finance; regional development; clustering; scientific approaches; statistical modeling method; clusters